Thermodynamic Parameters of PbTe Crystals: DFT-Calculations - Freik, D. M.; Volochanska, B. P.; Parashchuk, T. O. (Physics and Chemistry of Solid State, 2015)
Based on the analysis of the crystal NaCl type and electronic structure of cubic phase CdS crystals the cluster models have been built for calculation of the geometric and thermodynamic parameters. According to density functional theory (DFT) and using the hybrid valence base set B3LYP the temperature dependence of the energy ΔE and the enthalpy ΔH of formation, Gibbs free energy ΔG, entropy ΔS, specific heat at constant volume CV and pressure CP of the crystals have been found. The analytical expressions of the temperature dependences of presented thermodynamic parameters which was approximated from the quantum- chemical calculations data and with using mathematical package Maple 14 have been received.